1998
DOI: 10.1021/ja982192s
|View full text |Cite
|
Sign up to set email alerts
|

The Hydrogen Bond between Water and Aromatic Bases of Biological Interest:  An Experimental and Theoretical Study of the 1:1 Complex of Pyrimidine with Water

Abstract: The supersonic molecular beam (absorption millimeter wave and microwave Fourier transform) spectra of the 1:1 complex between pyrimidine and four isotopomers of water (H2O, HDO, D2O, and H2 18O) have been assigned. The derived moments of inertia are consistent with a planar (or nearly planar) structure of the adduct in which one hydrogen of the water molecule is bound to the nitrogen of the aromatic ring, and the “free” water hydrogen is entgegen to the ring. Only high level ab initio calculations (6-31G**+MP2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
82
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 31 publications
9
82
1
Order By: Relevance
“…[28] Figure 2 shows the three Lennard-Jones potential curves. As to the two Ne internal rotations their effects are reflected in their contribution to the negative values of DM xx and DM yy , as mentioned above, and to the anomalous high values of the D JK and D K centrifugal distortion parameters, as outlined in several of the complexes of aromatic molecules with rare gases.…”
Section: Geometrymentioning
confidence: 99%
“…[28] Figure 2 shows the three Lennard-Jones potential curves. As to the two Ne internal rotations their effects are reflected in their contribution to the negative values of DM xx and DM yy , as mentioned above, and to the anomalous high values of the D JK and D K centrifugal distortion parameters, as outlined in several of the complexes of aromatic molecules with rare gases.…”
Section: Geometrymentioning
confidence: 99%
“…Previous investigations of the rotational spectrum of PRM were mainly involved with analysis of the 14 N-quadrupole structure within the confines of the Doppler profile (3), or with double resonance experiments related to the generation of a a electric dipole moment component upon 13 C-and 15 N-asymmetric isotopic substitution (4). Recently we investigated in our laboratories the complexes of PRM with argon (5) and water (6) and found that a more detailed knowledge of the molecular properties of the PRM monomer was becoming necessary. In addition to the molecular structure, an accurate knowledge of the nuclear quadrupole tensor would facilitate more confident assignment of the orientation of PRM in a complex (6).…”
Section: Introductionmentioning
confidence: 99%
“…Recently we investigated in our laboratories the complexes of PRM with argon (5) and water (6) and found that a more detailed knowledge of the molecular properties of the PRM monomer was becoming necessary. In addition to the molecular structure, an accurate knowledge of the nuclear quadrupole tensor would facilitate more confident assignment of the orientation of PRM in a complex (6). For this reason we have undertaken a comprehensive study of the rotational spectrum of PRM at frequencies ranging from 3 to 337 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…An attempt was made to refine the scale factors using the set of transferable scale factors recommended by Pulay et al [18]. Vibrational frequencies calculated at HF/6-311G and B3LYP/6-311G levels were scaled by 0.8821 for wavenumbers less than 1700 cm -1 and 0.9811 for higher wavenumbers.…”
Section: Effect Of Multiple Scaling On Frequency Fit and Vibrational mentioning
confidence: 99%